ANALISIS AFEKTIVITAS TRANSMISI KEBIJAKAN MONETER GANDA DI INDONESIA MELALUI KEBIJAKAN SUKU BUNGA ACUAN BARU BI SEVEN DAYS REVERSE REPO RATE - SAPUTRA, RIZKY DWI (Jurnal Ilmiah Mahasiswa FEB, 2017)
Banking financial institutions in both conventional and sharia banks have an intermediary function, in which the function of collecting and channeling funds to the public so akahirnya can affect the economy by way of money circulating in the community. Where in circulating the money is strongly influenced by the total credit and financing by each conventional banking and sharia. Total credit and financing is one factor in influencing economic growth. Therefore, to know the effectiveness of total credit and financing to economic growth. It is necessary to analyze VAR / VECM that can determine the level of effectiveness of the policy in the long term and short term. So in the long- term and short-term results, financing in sharia banks is more optimal than credit. Due to financing here is not using the system of interest but the system for the results that do not burden mmasyarakat compared to the system of interest that people are difficult to restore and tend to bad credit. Therefore, financing can tend to affect the real sector and ultimately affect economic growth.Keyword: Bank, Credit, Economic Growth, Financing.